Protein‐Sized Dye‐Loaded Polymer Nanoparticles for Free Particle Diffusion in Cytosol. (11th October 2018) - Reisch, Andreas; Heimburger, Doriane; Ernst, Pauline; Runser, Anne; Didier, Pascal; Dujardin, Denis; Klymchenko, Andrey S.
Abstract: How small should nanoparticles be in order to travel freely through the cytosol similar to proteins? Answering this question remains a challenge, because the majority of nanoparticles are relatively large and their size cannot be finely tuned to match that of proteins. Here, poly(methyl methacrylate) copolymers with varied fraction and type of charged groups (carboxylate, sulfonate, and trimethylammonium) are developed, yielding nanoparticles with controlled sizes from 50 to 7 nm through nanoprecipitation. Loading these nanoparticles with a rhodamine dye/bulky counterion pair at 10wt% makes them highly fluorescent. After their coating with polyethylene glycol groups for preventing non‐specific protein binding and microinjection into living cells, the first systematic study of the size effect on diffusion in the cytosol for solid nanoparticles of the same nature is realized. Single‐particle‐tracking data provide evidence for distinct particle sieving in the cytosol, suggesting that only nanoparticles below a critical size of 23 nm exhibit free diffusion and spreading. These findings show the size limitations imposed by intracellular crowding and compartmentalization, which is critical for applications of nanomaterials in the cytosol. The proposed concept of polymer design opens the route to organic nanoparticles of ultrasmall sizes and high loading for bioimaging and drug‐delivery applications. Abstract : What is the ideal size of nanoparticles (NPs) for intracellular applications? Here, a series of dye‐loaded polymer NPs with sizes from 50 down to 7 nm is synthesized and microinjected into living cells. Single‐particle tracking of these particles suggests that only NPs smaller than a critical size of 23 nm exhibit free diffusion and spreading in the cytosol.